LAJU OKSIDASI TITANIUM MURNI (CPTI GRADE TIPE 340) BERLAPIS HYDROXYAPATITE (HA) YANG DISINTER DALAM TUNGKU PERLAKUAN PANAS - Desmarita Leni; Gunawarman Gunawarman; Jon Affi; Yuli Yetri (METAL: Jurnal Sistem Mekanik dan Termal, 2019)
Implants are used for various reasons, such as replacing damaged tissue caused by disease or trauma, as filler and support the healing phase. The general terminology of biocompatibility describes a condition which will not cause harmful interaction between foreign material and the body. Biocompatibility is a system  including physical, chemical, biological, medical, and design aspects. This study is focused on the influence of the coating thickness of hidroxyapatite layer on the rate of oxidation. Pure titanium  coated by HA with thickness variation needs to be tested for oxidation resistance to determine the  coating effectiveness in reducing the rate of oxidation. The rate of oxidation  measured by weight loss method after coated titanium by HA and than heating in a heat furnance. HA coatings obtained by a process of electrophoretic deposition (EPD) with  variation of time between  5 to 35 minutes at a voltage of 40 V with fineness of 30 µm. The oxidation process was done during the sintering process in a heat furnace for 10 minutes. The result of this study shows that the increase of time EPD increases the thickness of HA layer. Oxidation resistance on CPTi after HA coating does not cause the quality of pure titanium degraded in addition,  the oxidation resistance of HA increases from good grade to excellent grade. It shows that the formation of surface oxide slows down during sintering process.